Effects of social exclusion and physical pain in chronic opioid maintenance treatment: fMRI correlates - Bach, Patrick; Frischknecht, Ulrich; Bungert, Melanie; Karl, Damian; Vollmert, Christian; Vollstädt-Klein, Sabine; Lis, Stefanie; Kiefer, Falk; Hermann, Derik (European neuropsychopharmacology, 2019)
Opioids interact with systems processing pain and social stimuli. Both systems are crucial for responding to strains of everyday life and both are linked to relapse risk in opioid-dependent patients. The investigation of those systems seems essential to better understand opioid addiction as a whole. 17 patients on opioid maintenance treatment (OMT) and 21 healthy individuals underwent a functional magnetic resonance imaging (fMRI) social ball-tossing (Cyberball) paradigm simulating social inclusion and exclusion. In addition, painful and non-painful temperature stimuli were applied, in order to test pain sensitivity. Patients on OMT showed reduced pain sensitivity. Subjective pain was higher after social exclusion compared to social inclusion trials. In comparison to healthy controls, OMT patients felt less included and more excluded during inclusion and control conditions, and equally excluded during the social exclusion condition. Feelings of exclusion during the inclusion trials were associated with higher scores on the childhood trauma questionnaire. Across all conditions, OMT patients demonstrated decreased fMRI activation in the bilateral superior and middle occipital and bilateral cunei, the lingual gyri, as well as in the left fusiform gyrus (whole brain FWE-corrected). Comparing social exclusion and inclusion conditions, healthy individuals showed significant activation in brain areas related to social feedback and emotion processing, such as the anterior cingulate cortex, the insula and fusiform gyrus, whereas OMT patients showed no difference across conditions. As negative social affect is a potential trigger for relapse, patients might benefit from therapeutic strategies that enhance social integration.